Corporate memory records and information management in the knowledge age - Megill, Kenneth A. 1939- (Gale virtual reference library, 2005)
"Corporate memory is the body of active and historical information that an organization has that is worth sharing, managing and preserving to enable it to function effectively. This book describes the most up-to-date methods and approaches to this essential function, as well as the adoption of an international standard for record management. Aimed at records managers and archivists responsible for maintaining and managing information within an organization."--GVRL description.